2008
DOI: 10.1039/b801579a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of gallium alkoxides

Abstract: Homoleptic gallium tris(alkoxides) [Ga(OR) 3 ] 2 were prepared by the reaction of [Ga(NMe 2 ) 3 ] 2 (1) and excess ROH (R = CH 2 CH 2 NMe 2 (2), CH(CH 3 )CH 2 NMe 2 (3), C(CH 3 ) 2 CH 2 OMe (4), CH 2 CH 2 OMe (5)) in toluene at room temperature. Compounds 2-5 were isolated as colourless oils. The side-products, [Ga(OCH 2 CH 2 NMe 2 ) 2 Cl] ( 6), [Ga(OCH(CH 3 )CH 2 NMe 2 ) 2 Cl] ( 7) and [Ga(OC(CH 3 ) 2 CH 2 OMe)Cl 2 ] 2 (8) were also isolated in low yield during the synthesis of 2, 3 and 4, respectively. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…150 The precursors were synthesized via a 1 : 1 reaction of GaMe 3 with a donor-functionalised alcohol to yield the gallium mono-alkoxides, [Me 2 Ga(OCH 2 -CH 2 YR x )] 2 . 153 A solution to this was the use of an amine elimination route, which enabled the isolation of mono-, bis-and tris-alkoxides, which have all been used to produce films of Ga 2 O 3 via AACVD. 152 Monomeric gallium bis-alkoxides, of the type [ClGa(OCH 2 CH 2 YR x ) 2 ] could be isolated from the reaction of GaCl 3 .…”
Section: Gallium and Indium Oxidesmentioning
confidence: 99%
“…150 The precursors were synthesized via a 1 : 1 reaction of GaMe 3 with a donor-functionalised alcohol to yield the gallium mono-alkoxides, [Me 2 Ga(OCH 2 -CH 2 YR x )] 2 . 153 A solution to this was the use of an amine elimination route, which enabled the isolation of mono-, bis-and tris-alkoxides, which have all been used to produce films of Ga 2 O 3 via AACVD. 152 Monomeric gallium bis-alkoxides, of the type [ClGa(OCH 2 CH 2 YR x ) 2 ] could be isolated from the reaction of GaCl 3 .…”
Section: Gallium and Indium Oxidesmentioning
confidence: 99%
“…The structural preferences in these complexes are governed by the nature of R, M and L [13][14][15][16][17][18][19][20][21][22][23][24][25]. Recently we have described the synthesis of diorgano-gallium/-indium complexes containing internally functionalized anionic oxo ligands [9,10,26,27].…”
Section: Introductionmentioning
confidence: 98%
“…However, in order to exploit the full potential of CVD it is sometimes necessary to tailor the properties of the precursor in order to optimise process parameters such as deposition temperature, layer purity, uniformity and evaporation temperature. We have been investigating the deposition of gallium [13][14][15][16][17] and indium [18] oxide thin films using alkoxide precursors via both AACVD and LPCVD. We have shown that replacement of simple alkoxide groups by donor-functionalised alkoxides, such as dimethylamino ethoxide (dmae), can result in precursors with improved physical properties and enhanced CVD performance [13].…”
Section: Introductionmentioning
confidence: 99%
“…A range of diorganoalkoxometallanes of gallium and indium incorporating donor-functionalised alkoxides have been structurally characterised [12,14,[16][17][18][19][20][21]. In general, these compounds are synthesized either via the reaction of MR' 3 with an alcohol, or from the salt metathesis reaction of R' 2 MX and M'OR (M = Ga, In; M' = alkali metal, R' = Me, Et, X = halide) [1].…”
Section: Introductionmentioning
confidence: 99%